2022
DOI: 10.1177/09544054221105151
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of static performance for robot polishing system based on work stiffness evaluation

Abstract: Robot-assisted bonnet polishing system (RABPS) is widely used in the polishing of optical components due to its low cost, high efficiency and rapid polishing. However, due to the insufficient stiffness of the robot, it is easy to produce vibration in the machining process, which not only causes the size of the polishing contact area to deviate from the ideal value, but also affects the removal amount of workpiece. First, this paper analyzes the influence of robot system stiffness on the actual polishing area s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…The results indicated that the polishing efficiency increased by 1.5 times when compared with manual polishing, the consistency of the polished blade was better, and the surface roughness could reach Ra 0.24 μm. Pan et al [5] proposed a static stiffness optimization method for robots to eliminate the impact of vibration on the workpiece surface during robot machining. The reliability of the optimization was verified through simulation experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the polishing efficiency increased by 1.5 times when compared with manual polishing, the consistency of the polished blade was better, and the surface roughness could reach Ra 0.24 μm. Pan et al [5] proposed a static stiffness optimization method for robots to eliminate the impact of vibration on the workpiece surface during robot machining. The reliability of the optimization was verified through simulation experiments.…”
Section: Introductionmentioning
confidence: 99%